Visual and hydraulic techniques produce similar estimates of cavitation resistance in woody species. Issue 3 (26th July 2020) - Gauthey, Alice; Peters, Jennifer M. R.; Carins‐Murphy, Madeline R.; Rodriguez‐Dominguez, Celia M.; Li, Ximeng; Delzon, Sylvain; King, Andrew; López, Rosana; Medlyn, Belinda E.; Tissue, David T.; Brodribb, Tim J.; Choat, Brendan
Summary: Hydraulic failure of the plant vascular system is a principal cause of forest die‐off under drought. Accurate quantification of this process is essential to our understanding of the physiological mechanisms underpinning plant mortality. Imaging techniques increasingly are applied to estimate xylem cavitation resistance. These techniques allow for in situ measurement of embolism formation in real time, although the benefits and trade‐offs associated with different techniques have not been evaluated in detail. Here we compare two imaging methods, microcomputed tomography (microCT) and optical vulnerability (OV), to standard hydraulic methods for measurement of cavitation resistance in seven woody species representing a diversity of major phylogenetic and xylem anatomical groups. Across the seven species, there was strong agreement between cavitation resistance values (P50 ) estimated from visualization techniques (microCT and OV) and between visual techniques and hydraulic techniques. The results indicate that visual techniques provide accurate estimates of cavitation resistance and the degree to which xylem hydraulic function is impacted by embolism. Results are discussed in the context of trade‐offs associated with each technique and possible causes of discrepancy between estimates of cavitation resistance provided by visual and hydraulic techniques.